Liderazgo Transformacional y Diferencias de Género en una Empresa Pública de Movilidad. “Caso de Estudio Empresa Pública de Movilidad de la Mancomunidad de Cotopaxi” - Santamaría Tipantásig, Mercy Antonieta (2022)
This Project aimed the objective to identify the relationship between transformational leadership and the gender of the Public Mobility Company of Cotopaxi through the investigation of theories and administrartive aproaches that contribute conceptually the relationship that exists between these variables.The establishment of the relationship that exists between transformational leadership and gender in the entity and the proposal of a transformational leadership model.It was based on the quantitative methodological approach of a descriptive and correlational type, with the use of MLQ questionary, with the participation of Company workers distributed in 41 men and 25 women.The hypothesis testing with R of Pearson gave an asymptotic significance value of 0.173 in which is greater than 0.005 with which establishes a positive correlation between transformational leadership and the entity gender. We were established as new leadership factors of transformational leadership with the proposed model: emotional intelligence, training an tutoria, motivation and positive development, cooperation and open communication, conviction and positive influence, positive interaction between collaborators and team workers